Roach (Rutilus rutilus) populations respond to varying environment by altering size structure and growth rate - Olin, M.; Rask, M.; Estlander, S.; Horppila, J.; Nurminen, L.; Tiainen, J.; Vinni, M.; Lehtonen, H. (Boreal Environment Research Publishing Board, 2024)
To better understand the environmental factors and biological interactions affecting roach abundance and population structure in oligo-mesotrophic lakes, we explored roach population parameters in 24 small forest lakes in southern Finland. In those lakes, roach abundance was only little affected by the abiotic and biotic variables such as lake characteristics, water transparency, nutrient concentrations, pH or related variables, predation and competition. This was probably due to the generalist characteristics of the roach as it is adaptive to a wide variety of environments. Instead, the population structure and age-specific growth of the roach were strongly affected by various environmental variables. The growth rate was negatively related to water colour, calcium and nutrient concentration and roach abundance, and positively related to perch abundance and lake size. The growth patterns and relatively stable abundance showed flexibility in adaptation to different environmental conditions. Our results indicate that the ongoing environmental changes, recovery from acidification and brownification may notably affect the structure and production of roach populations, and may alter the role of the roach in lake ecosystems